Profitability and cost estimates for producing Mango (Mangifera Indica L.) in south Florida - Trent Blare; Fredy BALLEN; Aditya Singh; Nicholas Haley; Jonathan Crane (EDIS, 2022)
This publication provides an estimate of the costs and returns associated with an established mango orchard in south Florida. It demonstrates that mangos are a profitable alternative for growers in south Florida, with growers earning on average $4,487/acre/year or $0.24/pound, which is larger than many other tropical fruits. Information in this publication will be useful to current and future mango growers, wholesalers, and processors interested in expanding the mango industry in south Florida.